2021
DOI: 10.1111/1468-5973.12383
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of fatalism belief and optimism orientation on seismic preparedness: Considering their roles in the nexus between risk perception and preparedness

Abstract: Despite the numerous studies focused on the sociopsychological factors involved in seismic preparedness, we have limited knowledge of the impact pathways from fatalism belief and optimism orientation to preparedness. This study proposed a theoretical model to examine the intertwined relationships among fatalism belief, optimism orientation, and risk perception regarding public seismic preparedness based on a survey in the Beijing-Tianjin-Hebei region in China. The results indicate that fatalism belief can dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 82 publications
(175 reference statements)
1
16
0
Order By: Relevance
“…Previous studies have indicated that fatalism takes various forms in different cultural contexts (Maercker et al, 2019; Sun et al, 2018); thus, context-specific measurement of fatalistic disaster beliefs should be adopted according to the actual local context. We find that there is a proverb widely shared in the Beijing–Tianjin–Hebei region of China, called “ Xiao zhen bu yong pao, da zhen pao bu liao ” (Liu and Sun, 2022; Sun et al, 2022). This proverb implies that there is nothing that one needs to do or can do to protect oneself from earthquakes.…”
Section: Research Design1mentioning
confidence: 93%
See 4 more Smart Citations
“…Previous studies have indicated that fatalism takes various forms in different cultural contexts (Maercker et al, 2019; Sun et al, 2018); thus, context-specific measurement of fatalistic disaster beliefs should be adopted according to the actual local context. We find that there is a proverb widely shared in the Beijing–Tianjin–Hebei region of China, called “ Xiao zhen bu yong pao, da zhen pao bu liao ” (Liu and Sun, 2022; Sun et al, 2022). This proverb implies that there is nothing that one needs to do or can do to protect oneself from earthquakes.…”
Section: Research Design1mentioning
confidence: 93%
“…In extant studies dealing with seismic behavior, fatalism has been found to be pervasive in earthquake-related thinking (Baytiyeh and Naja, 2014;Joffe et al, 2013Joffe et al, , 2019McClure et al, 2007;Solberg et al, 2010;Yari et al, 2019). Similarly, previous studies have reported that a kind of fatalistic seismic belief that encourages taking no action in the face of an earthquake was endorsed by some local residents in the Beijing-Tianjin-Hebei area (Liu and Sun, 2022;Sun et al, 2022). Sun et al (2022) further indicated that previous earthquake experience and a general fatalistic orientation partly account for the formation of the fatalistic seismic belief of some people in the Beijing-Tianjin-Hebei area.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations